Making sense of war : the Second World War and the fate of the Bolshevik Revolution - Weiner, Amir 1961- (Princeton Univ. Press, 2001)
Machine generated contents note: PART I: DELINEATING THE BODY POLITIC -- One -- Myth and Power: The Making of a Postwar Elite -- Two -- "Living Up to the Calling of a Communist": Purification -- of the Rank and File -- PART II: DELINEATING THE BODY SOCIOETHNIC -- Three -- Excising Evil -- Four -- Memory of Excision, Excisionary Memory -- PART m: THE MAKING OF A POSTWAR SOVIET NATION -- Five -- Integral Nationalism in the Trial of War -- Six -- Peasants to Soviets, Peasants to Ukrainians -- Afterword: A Soviet World without Soviet Power, -- a Myth of War without War -- Bibliography -- Index